Re-examining the decline in the US saving rate: The impact of mortgage equity withdrawal - Guglielmo Maria Caporale; Mauro Costantini; Antonio Paradiso (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
In this paper we examine the role of mortgage equity withdrawal in explaining the decline of the US saving rate, since when house prices rise and mortgage rates are low, homeowners have an incentive to withdraw housing equity and this may affect the saving rate. We estimate a Vector Error Correction (VEC) model including the saving rate, asset prices, equity withdrawal and interest rates and find that indeed mortgage equity withdrawal is a key determinant of the observed saving pattern.
Keywords: C32; E21; O51; 330; Saving rate; Mortgage equity withdrawal; Asset prices; Mortgage rates; Vector Error Correction; Impulse response analysis